Nasal and nasopharyngeal Burkitt’s lymphoma in pediatric age group – A review - Swain, Santosh (Indian Journal of Child Health, 2022)
Burkitt’s lymphoma (BL) is an aggressive variety of non-Hodgkin’s lymphoma where a neoplastic monoclonal proliferation of the lymphoid cells occurs at the site of the immune system. BL is commonly related to human immunodeficiency virus infections, EBV infections, and malaria-endemic region. BL at the nasal cavity and nasopharynx in pediatric age is extremely rare and often spread to the skull base and brain rapidly. It often presents with non-specific symptoms which lead to misdiagnosis and delayed treatment. The symptoms of pediatric patients with nasal and nasopharyngeal BL are range from obstruction of the nasal cavity to recurrent nasal bleeding, headache, and facial pain. The diversity of the symptomatology of this clinical entity is mostly associated with the anatomical location of this tumor. Late diagnosis or misdiagnosis usually causes a fatal outcome. Hence, early identification and treatment improve the prognosis of pediatric nasal and nasopharyngeal BL. Histopathology and immunohistochemistry usually confirm the diagnosis. This aggressive and rapidly growing lymphoma is curable and highly sensitive to chemotherapy. Early diagnosis and prompt treatment are the important aspects of preventing complications and curing BL. This review article aims to discuss the nasal and nasopharyngeal BL in pediatric age including its epidemiology, etiopathology, investigations, and current treatment. It will also catalyze additional studies for BL.